Forgive : why should I and how can I? - Keller, Timothy, 1950- (Viking, 2022)
"Forgiving anyone in a meaningful way is one of the hardest things a person has to do. If you do not, resentment and vengeance begin to consume you. It is nearly impossible to move past transgression without forgiveness, but few people have the resources and the tools to forgive others fully and move on with their lives. Forgiveness is an essential skill, a moral imperative, and a religious belief that cuts right to the core of what it means to be human. In Forgive, Timothy Keller shows readers why it is so important and how to do it, explaining in detail the steps you need to take in order to move on without sacrificing justice or your humanity"--